NURSES' PERCEPTION OF THEIR COMPETENCIES IN THE PROVISION OF PSYCHIATRIC CARE: A CASE OF LOITOKITOK SUB-COUNTY HOSPITAL - Wanjiru, Muchene; Ntoiti, Peter; Gathigia, Ruth (Journal of Health, Medicine and Nursing, 2021)
Purpose: The main purpose of this study was to assess nurses' self-evaluation of their competencies in the care of psychiatric patients at Loitoktok Sub-County Referral Hospital. Methodology: A cross-sectional study, employing census survey of all the 41 eligible nurses working in the hospital was done. A structured questionnaire was used to collect data. Informed voluntary consent and all other ethical clearances were obtained. The data obtained was analyzed using SPPS version 20. Findings: Majority of nurses were from maternity department. On gender aspect, female nurses were more than male nurses. Most nurses had strong perceived competency in provision of psychiatric care especially in the area of therapeutic communication. The perceived competency did not significantly differ across the nurses' qualification, neither did it significantly vary from one department to another. However, the study revealed significant variation in perceived competency across the various years of experience. Moreover, the perceived competency in conducting psychiatric assessment had a significant influence on the ability to provide psychiatric care. Likewise, the perceived intervention competency had an influence on the ability to provide care. However, there was no relationship between perceived communication competency and ability to provide psychiatric care. Unique contribution to theory, practice and policy: There is need for regular assessment of nurses' competencies to form need based capacity building, especially for nurses with more than four years' experience; and exploring opportunities of encouraging nurses to seek assistance with competencies they have deficiencies in.